A view behind the scene: data structures and software architecture of a VAA - Tsapatsoulis, Nicolas; Djouvas, Constantinos (My University, 2014)
In today's rapidly evolving and growing online community many different applications are proposed and implemented. One category of such applications that drew high attention during the last few years are the so-called Voting Advice Applications (VAAs). VAAs are online systems used during elections that allow voters to create a political profile, the comparison of this profile with the profiles of political parties and candidates provides the voter with an estimation of his/her proximity to parties and candidates. In this paper, the data structure and the software architecture used for implementing a VAA platform along with its technical requirements are presented. Furthermore, a novel approach used for supporting multi-lingual content is described.
Keywords: Voting Advice Applications; Data structures; Semantics; Social networking (online); Software architecture; On-line communities; Political parties; Technical requirement